Assessment of heavy metal contamination in intertidal gastropod and bivalve shells from central Arabian Gulf coastline, Saudi Arabia. (November 2015) - El-Sorogy, Abdelbaset S.; Youssef, Mohamed
Abstract: In order to assess pollutants and impact of environmental changes along the Saudi Arabian Gulf coast, forty specimens of gastropod and bivalve shells belonging to Diodora funiculata, Lunella coronata, Cerithium caeruleum, Barbatia parva, Pinctada margaritifera, Amiantis umbonella, Acrosterigma assimile and Asaphis violascens from five localities are selected for Fe, Cu, Pb, Mn, Cd, Se, As, Co, B, Cr, Hg, Mo analysis. The analysis indicated that heavy metal values (except Fe) were less than those recorded in molluscan shells from Gulf of Oman, Red Sea and Indian Ocean. D. funiculate, L. coronata, B. parva and P. margaritifera are good accumulators of Cu, As, Cr. The other species gave a nearly constant concentration in all the studied areas. Al Jubail coast recorded the highest heavy metal concentrations (except Mn at Ras Al-Ghar and Se at Al Jubail industrial city). Heavy metal contamination is mostly attributed to anthropogenic sources, especially effluents from petrochemical industries, sewage and desalination plants. Highlights: The present work deals with the environmental assessment of Saudi Arabian Gulf. 40 shells have been analyzed for Fe, Cu, Pb, Mn, Cd, Se, As, Co, B, Cr, Hg, Mo. Al Jubail coast recorded the highest concentrations. Diodora, Lunella, Barbatia and Pinctada are good accumulators for Cu, As, Cr.